2015
DOI: 10.1016/j.sdj.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of incidence of dentinal defects after root canal preparation with continuous rotation and reciprocating instrumentation

Abstract: Biomechanical preparation is one of the most important steps in endodontic therapy. Rotary instrumentation has facilitated this step. Nowadays the market is flooded with different types of rotary instruments. The present study compared the root dentinal crack formation with continuous rotating versus reciprocating root canal preparation methods. One hundred and fifty freshly extracted teeth were used for the study. They were divided into 5 groups with 30 teeth in each group. Thirty teeth were kept under contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…Of those studies, 12 were excluded after we examined the full text because they did not conform to the eligibility criteria of this review, as shown in Table 2 20,30-40) . Finally, the 8 studies that met the inclusion criteria were included [21][22][23][24][25][26][27][28] . The process involved in the study selection is shown in Fig.…”
Section: Literature Searchmentioning
confidence: 99%
See 4 more Smart Citations
“…Of those studies, 12 were excluded after we examined the full text because they did not conform to the eligibility criteria of this review, as shown in Table 2 20,30-40) . Finally, the 8 studies that met the inclusion criteria were included [21][22][23][24][25][26][27][28] . The process involved in the study selection is shown in Fig.…”
Section: Literature Searchmentioning
confidence: 99%
“…Two studies 23,27) compared ProTaper and Reciproc. Five studies 22,[24][25][26]28) compared ProTaper and WaveOne. One study included both of the two comparison groups 21) .…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations